A Management Decision Process for Corporate Action - Jeli nata liyas; Rahmi Fahmy (International Journal of Islamic Business and Management Review, 2021)
Corporate Action namely every action of the issuer that gives equal rights to all shareholders such as Dividends, Right Issues and Stock Splits. Dividend is the distribution of company profits to shareholders based on the percentage of ownership of capital owners. Management decisions in seeking new capital or funds through the stock exchange floor are usually for debt repayment actions, company goals, expansion through product innovation in improving and maintaining company stability for better prospects in the future so as to encourage the government to build a better economy in the next period. Corporate action applies to all companies, not limited to public companies. Several forms of corporate action that are generally carried out by issuers include the distribution of dividends, both cash and shares,